Government of Republic of South Sudan Public Finance Management Assessment : Jonglei State - World Bank (Washington, DC, 2014)
A public finance management (PFM) law is still not in place, even though a draft was prepared more than three years ago. The purpose is to assess the PFM system performance of Jonglei State in South Sudan. This report feeds into a Country Fiduciary Risk Assessment (CIFA) along with a South Sudan Public Expenditure Financial Accountability (PEFA) assessment country procurement assessment report being prepared by a World Bank team on Republic of the Republic of South Sudan (GRSS's) procurement system, using the OECD-DAC assessment methodology, and with PFM diagnostics study on three other state governments. The CIFA will include an action plan for implementing PFM reforms. This PEFA is focused on the State Government of Jonglei. At the time of this PEFA assessment, South Sudan, then known as Southern Sudan, was a semi-autonomous part of Sudan managed by Government of Southern Sudan (GoSS), as part of the Government of National Unity (GoNU) that included both GoSS and the Government of Sudan ('the north'). Jonglei is the largest state in South Sudan, both by area (estimated at 122,581 square kilometers) and by population (1,358,602 people). Socioeconomic development activities have been guided by the Jonglei State strategic plan 2007 to 2011 (published in June 2007). A key challenge is insecurity, partly because of tribal conflict. Instances of violence are common, even as recent as a clash between the Sudan Peoples' Liberation Army (SPLA) and a militia in February 2011. The state does not have its own law governing PFM. As indicated in the PEFA assessment for GoSS, a PFM bill awaits approval by the State Legislative Assembly (SLA), and this would govern PFM legislation at the state government level. In the absence of a state level procurement law, the GoSS level interim procurement and disposal guidelines govern procurement in Jonglei State.